The role of IL-1β in the development of diabetes mellitus - Zaiats, Liubomyr; Fedorchenko, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2022)
Background. Currently, diabetes mellitus is the most common of all endocrine diseases with increasing tendency. The purpose of our research was to study the dynamics of serum levels of proinflammatory cytokine-IL-1β in streptozotocin-induced diabetes. Materials and methods. The experiments were performed on 88 white male Wistar rats weighing 170-210 g. Animals were divided into three groups: 1 - intact; 2 - control; 3 - experimental with a model of diabetes mellitus, which was reproduced by intraperitoneal injection of streptozotocin by “Sigma" company (USA), diluted in 0.1 M citrate buffer with a pH of 4.5, at a rate of 60 mg/kg body weight. The control group of animals received an intraperitoneal injection with an equivalent dose of 0.1 M citrate buffer solution with a pH of 4.5. All studies were performed under thiopental-sodium anesthesia at a rate of 60 mg/kg body weight. Serum levels of IL-1β were determined by enzyme-linked immunosorbent assay (ELISA) kit (Elabscience, USA) according to the manufacturer's instructions 14, 28, 42 and 70 days after streptozotocin injection. The STATISTICA 10 program was used for statistical processing of the obtained results. Results. Conducted biochemical analysis showed that in animals with streptozotocin-induced diabetes there was an increase in the content of proinflammatory cytokine IL-1β compared with similar indicators in the control group of animals at all stages of the experiment: after 14 days by 22.5%, after 28 days by 40.2%, after 42 days by 72.8% and after 70 days by 107.2%. Conclusion. The obtained results suggest that pro-inflammatory cytokine interleukin-1β plays one of the leading roles in the pathogenesis of streptozotocin-induced diabetes, as indicated by a significant increase in serum of this cytokine at all stages of the experiment.